Intergenerational Environmental Rights: Reading the Istikhlaf Verse as a Sustainable Legal Doctrine - Shuhada, Muhammad Aula Rahmad (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2026)
This article examines the istikhlaf verses of QS. Al-Baqarah [2]: 30, QS. Al-An'am [6]: 165, QS. Hud [11]: 61, and QS. al-Rum [30]: 41. From the perspective of ecological inheritance law, arguing that future generations have the right to Islamic law (huquq shar'iyyah) over a clean and sustainable earth, just as heirs have the right to undivided inheritance. Using a qualitative approach grounded in a literature review and the Maudhu'i interpretation method, this study examines the interpretations of classical and contemporary exegetes. Then it develops a legal analogy (qiyas) between the structure of Islamic inheritance law (faraid) and the rights of future generations over the environment. The results of the study show that the concept of amanah, mizan, and the prohibition of fase fi al-ard places the current generation as wasi (will holder) of the earth's assets, not absolute owners, so that exploitation that reduces the rights of future generations is equivalent to itlaf mal al-ghair in muamalah fiqh. This study finds a conceptual meeting point with Edith Brown Weiss's doctrine of intergenerational equity. It concludes that the ecological rights of future generations can be formulated as part of the maqashid sharia, especially hifz al-bi‘ah as an extension of hifz al-nasl.